Critical Human Rights, Citizenship, and Democracy Education Entanglements and Regenerations - Zembylas, Michalinos; Keet, André (Bloomsbury Critical Education, 2018)
Critical Human Rights, Citizenship, and Democracy Education presents new scholarly research that views human rights, democracy and citizenship education as a critical project. Written by an international line-up of contributors including academics from Canada, Cyprus, Ireland, South Africa, Sweden, the UK and the USA, this open access book provides a cross-section of theoretical work as well as case studies on the challenges and possibilities of bringing together notions of human rights, democracy and citizenship in education. The contributors cultivate a critical view of human rights, democracy and citizenship and revisit these categories to advance socially just educational praxis and highlight ground-breaking case studies that redefine the purposes and approaches in education for a better alignment with the justice-oriented objectives of human rights, democracy and citizenship education. A critical response, reflecting on the issues raised throughout the book, provides a conclusion. This is essential reading for those researching these pedagogical forms and will be valuable to practitioners and activists in fields as diverse as education, law, sociology, health sciences and social work and international development. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Knowledge Unlatched.